FORMATION OF RESEARCH COMPETENCE IN FUTURE EDUCATION MANAGERS - Valentyna Hladkova (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article reveals the essence of research competence and the peculiarities of its formation in future education managers. The methodological basis of the research is made up of methodological approaches: systemic, competence-based, synergistic, complex. The most significant is the acmesynergetic approach. The methodological basis of the study is also made up of methodological principles: intentional dynamism; invariance; individualization; simultaneous study of a person and his activities; systemic and structural; historicism; humanism; development; determinism - self-determinism, etc. Clarification of the definition of the concept of «research competence» is a set of knowledge, research skills (a set of intellectual, practical and organizational skills), skills, research abilities (heuristic, creativity, intellectual mobility, anticipation, independence and impartiality of thinking, emotional intelligence, self-reflection), ways performing actions in situations of uncertainty, in conditions of lack or excess of information, etc. Research competence includes the following components: consistency, prevention, innovation, predictability (acmeological). To assess the level of formation of research competence, the levels (reproductive, adaptive, productive, creative), criteria (motivational-value, practical, reflexive) and the corresponding indicators were determined. A complex of pedagogical conditions providing the formation of research competence of future education managers has been determined. These are: the development of the research potential of undergraduate students based on the actualization of the inner resources of the individual in the process of mastering professional disciplines; stimulating undergraduates to research activities by involving them in solving advanced cognitive and experimental-creative tasks of a professionally oriented nature when using various forms and methods of organizing the educational process; inclusion of undergraduates in different types of research work in the educational process during pre-diploma practice and performance of qualifying (master's) work. The positive nature of the influence of pedagogical conditions on the formation of the research competence of future education managers in the conditions of a master's degree is confirmed by the results of control sections at the final stage of the research.